THE IMPACT OF COMPENSATION, TRANSFORMATIONAL LEADERSHIP, AND EMPLOYEE SATISFACTION TOWARD EMPLOYEE PERFORMANCE - Cristy Gomgom Ebenzer Sitorus; Rr Erlina; Nova Mardiana (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
Employee performance in the banking industry is decisive to compete globally. Compensation, transformational leadership, and employee satisfaction are important factors to improve employee performance. This study aims to examine benefits, transformational leadership, and employee satisfaction and its effect on the performance of employees of PT. Bank Negara Indonesia (Persero) Tbk Metro Branch Office, Lampung. The data collection method uses a questionnaire distributed to all employees of 54 people. The analytical tool used is multiple linear regression. This study presents that all data is valid and reliable and meets the classical regression assumptions. The results of the study explained that compensation, transformational leadership, and employee satisfaction have positive and partially positive effects on employee performance.